An objective and individualised method of predicting performances in running events - Watt, R. (New Studies in Athletics, 2013)
Often we are interested in attempting to get an estimate of the performance that an athlete should achieve in an athletics event. This may be for training purposes (i.e. since training is often over distances that are not commonly raced, we would like to know what our athlete is capable of in that distance at 100% in order to set realistic objectives for intervals), or perhaps to be able to compare an achieved performance against what the athlete should have been theoretically capable of, in order to judge the value of the performance. In this paper the author provides a method for doing this, based entirely on objective data of the athlete him/herself, i.e. without recourse to information on other athletes, or to guess-work, at all. Two performances over distances that are within the athlete`s range of competence are needed in order to obtain an estimate of the athlete`s capability over any other distance also within the range of competence. The methodology is shown to be accurate to within only a few percentage points by means of considering the actual and predicted times of some top international athletes.